Relation between occupant perception of brightness and daylight distribution with key geometric characteristics in multi-family apartments of Malmö, Sweden. (November 2019) - Bournas, Iason; Dubois, Marie-Claude; Laike, Thorbjörn
Abstract: Focusing on subjective evaluations of daylight conditions, the present paper explores the relation between room geometric characteristics and perceived brightness and daylight distribution in residential spaces. The study was conducted in 35 apartments consisting of 105 different rooms in the city of Malmö, and selected with respect to typical Swedish architectural building typologies. Questionnaires were distributed by mail to participants, and apartments were surveyed to deduct key geometric characteristics. Results include a reliability analysis of the utilized questionnaire and a correlation study that showed the prevalence of both window size and number as key factors relating to perceived daylight conditions.